Optimization of soaking conditions in parboiling using response surface methodology to enhance the properties of MR297 rice cultivar - Muchlisyiyah, Jhauharotul; Shamsudin, Rosnah; Kadir Basha, Roseliza; Shukri, Radhiah; How, Syahmeer; Mohd Basri, Mohd Salahuddin (Informa Healthcare, 2025)
MR297 is known as a resistant cultivar to rustic disease but has a low head rice yield. The purpose of this study was to optimize the soaking conditions (temperature and time) for the enhancement of quality characteristics of long grain rice cultivar MR297 parboiled The experiment was done by optimizing the effects of soaking temperature (50–70 °C) and soaking time (2–4 h) for paddy using a central composite design of response surface methodology. The parboiling process then continued with steaming 100 °C for 20 min and drying 38 °C for 24 h). Besides analyzing the physical properties and milling properties of parboiled rice, the color and hardness properties of parboiled milled rice varieties were also investigated. We used design expert software to optimize the responses numerically. MR297 parboiled rice quality was significantly affected by the temperature and soaking time (p < 0.05). It was found that 54.75 °C and 2 h of soaking was the optimal temperature and time. The optimization was done to maximize the head rice yield, maximize the hardness, maximize the lightness, and also minimizing the browning index and total color change of the milled rice during parboiling, the proposed suggestion should be implemented.